Jesus camp [videorecording (DVD)] - Ewing, Heidi E.; Grady, Rachel; Fischer, Becky, 1951- (Magnolia Home Entertainment, 2006)
A first-ever look into an intense training ground that recruits born-again Christian children to become an active part of America's political future. Follow these children at summer camp in Devil's Lake, North Dakota as they hone their 'prophetic gifts'.